Preserved frontal lobe oxygenation following calcium chloride for treatment of anesthesia-induced hypotension - Kitchen, Carl-Christian; Nissen, Peter; Secher, Niels H.; Nielsen, Henning B. (Frontiers in Physiology, 2014)
Vasopressor agents may affect cerebral oxygenation (rScO2) as determined by near-infrared spectroscopy on the forehead. This case series evaluated the effect of calcium chloride vs. α and β-adrenergic receptor agonists on rScO2 in patients (n = 47) undergoing surgery during i.v. anesthesia. Mean arterial pressure (MAP) and cardiac output (CO) were assessed by Model-flow® and ephedrine (55 ± 3 vs. 74 ± 9 mmHg; 10 mg, n = 9), phenylephrine (51 ± 5 vs. 78 ± 9 mmHg, 0.1 mg, n = 11), adrenaline (53 ± 3 vs. 72 ± 11 mmHg; 1 - 2 µg, n = 6), noradrenaline (53 ± 5 vs. 72 ± 12 mmHg; 2-4 µg, n = 11), and calcium chloride (49 ± 7 vs. 57 ± 16 mmHg; 5 mmol, n = 10) increased MAP (all P < 0.05). CO increased with ephedrine (4.3 ± 0.9 vs. 5.3 ± 1.2, P < 0.05) and adrenaline (4.7 ± 1.2 vs. 5.9 ± 1.1 l/min; P = 0.07) but was not significantly affected by phenylephrine (3.9 ± 0.7 vs. 3.6 ± 1.0 l/min), noradrenaline (3.8 ± 1.2 vs. 3.7 ± 0.7 l/min), or calcium chloride (4.0 ± 1.4 vs. 4.1 ± 1.5 l/min). Following administration of β-adrenergic agents and calcium chloride rScO2 was preserved while after administration of α-adrenergic drugs rScO2 was reduced by app. 2% (P < 0.05). Following α-adrenergic drugs to treat anesthesia-induced hypotension tissue oxygenation is reduced while the use of β-adrenergic agonists and calcium chloride preserve tissue oxygenation.